Empiryczna ocena dokładności zwykłych wzorów dendrometrycznych dla strzał bez kory modrzewia europejskiego Larix decidua Mill. - Hawranik, Łukasz; Tomusiak, Robert (Leśne Prace Badawcze, 2022)
To determine the volume of felled trees, dendrometric formulas are used that are the product of a specific cross-section and the length of a dendrometric solid. In order to apply these formulas on a larger scale, it is essential to know their accuracy. Most of the research on the accuracy of dendrometric formulas has been carried out using Scots pine with other tree species, including European larch Larix decidua Mill., often being overlooked. The aim of this study was to assess the accuracy of eight common dendrometric formulas for stems of European larch without bark. The research material consisted of 290 larch stems from two forest districts (Pińczów and Prudnik), representing trees from age classes II to V and older. The following formulas were observed to be highly accurate: Huber’s, French, Hossfeld’s, Gieruszynski’s and the two-halfs formula. Huber’s formula provided the mean value of percentage errors closest to zero (0.8%) and was the most accurate formula, whereas the two-halfs formula, showed the lowest variability of percentage errors (standard deviation 3.1%). However, all formulas tended to generate systematic errors with the merchant’s and two-halfs formulas underestimating the volume, while the others overestimated the volume. Most of the formulas´ accuracy was uniform across the different age classes with the exception of the Smalian’s and Rieckie-Newton’s formulas, that were significantly less accurate when applied to the V and older age classes, and the merchant’s formula, characterized by greater accuracy in the V and older age classes. Pair-wise comparisons of the formulas´ accuracy revealed significant differences between most of the analyzed pairs of formulas though no differences were found between the French and Gieruszynski, French and Hossfeld, Gieruszynski and Hossfeld, Gieruszynski and Huber formulas as well as between the Hossfeld and Huber formulas.